Periprosthetic bacterial biofilm and quorum sensing. Issue 9 (24th May 2018) - Mooney, Jake A.; Pridgen, Eric M.; Manasherob, Robert; Suh, Gina; Blackwell, Helen E.; Barron, Annelise E.; Bollyky, Paul L.; Goodman, Stuart B.; Amanatullah, Derek F.
ABSTRACT: Periprosthetic joint infection (PJI) is a common complication after total joint arthroplasty leading to severe morbidity and mortality. With an aging population and increasing prevalence of total joint replacement procedures, the burden of PJI will be felt not only by individual patients, but in increased healthcare costs. Current treatment of PJI is inadequate resulting in incredibly high failure rates. This is believed to be largely mediated by the presence of bacterial biofilms. These polymicrobial bacterial colonies form within secreted extracellular matrices, adhering to the implant surface and local tissue. The biofilm architecture is believed to play a complex and critical role in a variety of bacterial processes including nutrient supplementation, metabolism, waste management, and antibiotic and immune resistance. The establishment of these biofilms relies heavily on the quorum sensing communication systems utilized by bacteria. Early stage research into disrupting bacterial communication by targeting quorum sensing show promise for future clinical applications. However, prevention of the biofilm formation via early forced induction of the biofilm forming process remains yet unexplored. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2331–2339, 2018. Abstract : Periprosthetic joint infection continues to be a common complication after total knee and hip arthroplasty leading to severe morbidity and mortality. This is believed to be largely mediated by the presence of bacterial biofilms, heavily reliant on quorum sensing communication systems. Early stage research into disrupting bacterial communication by targeting quorum sensing show promise for future clinical applications. However, prevention of the biofilm formation via early forced induction of the biofilm forming process remains yet unexplored.